The interval between progression and therapy initiation is the key prognostic parameter in relapsing diffuse large B cell lymphoma: analysis from the Czech Lymphoma Study Group database (NIHIL) - Janikova, Andrea; Michalka, Jozef; Bortlicek, Zbynek; Chloupkova, Renata; Campr, Vit; Kopálová, Nataša; Klener, Pavel; Benesova, Katerina; Hamouzova, Jitka; Belada, David; Prochazka, Vit; Pytlik, Robert; et al. (Annals of hematology, 2020)
Relapsing diffuse large B cell lymphomas (rDLBCL) represent a heterogeneous disease. This heterogeneity should be recognized and reflected, because it can deform the interpretation of clinical trial results. DLBCL patients with the first relapse and without CNS involvement were identified in the Czech Lymphoma Study Group (CLSG) database. Interval-to-therapy (ITT) was defined as the time between the first manifestation of rDLBCL and the start of any treatment. The overall survival (OS) of different ITT cohorts (< 7 vs. 7-21 vs. > 21 days) was compared. In total, 587 rDLBCLs (51.8% males) progressed with a median of 12.8 months (range 1.6 to 152.3) since the initial diagnosis (2000-2017). At the time of relapse, the median age was 67 years (range 22-95). First-line therapy was administered in 99.3% of the patients; CHOP and anti-CD20 were given to 69.2% and 84.7% of the patients, respectively. The salvage immune/chemotherapy was administered in 88.1% of the patients (39.2% platinum-based regimen). The median ITT was 20 days (range 1-851), but 23.2% of patients initiated therapy within 7 days. The 5-year OS was 17.4% (range 10-24.5%) vs. 20.5% (range 13.5-27.4%) vs. 42.2% (range 35.5-48.8%) for ITT < 7 vs. 7-21 vs. > 21 days (p < 0.001). ITT was associated with B symptoms (p 0.004), ECOG (p < 0.001), stage (p 0.002), bulky disease (p 0.005), elevated LDH (p < 0.001), and IPI (p < 0.001). The ITT mirrors the real clinical behavior of rDLBCL. There are patients (ITT < 7 days) with aggressive disease and a poor outcome. Conversely, there are rDLBCLs with ITT ≥ 21 days who survive for a long time.
Keywords: recidiva; neoadjuvantní terapie; Vincristine; Humans; lidé středního věku; Disease Progression; kohortové studie; doxorubicin; Aged; mladý dospělý; dospělí; protokoly protinádorové kombinované chemoterapie; databáze faktografické; Doxorubicin; Female; Prednisone; výsledek terapie; Time-to-Treatment; senioři; lidé; Databases, Factual; Cohort Studies; Adult; čas zasáhnout při rozvinutí nemoci; prednison; ženské pohlaví; Male; rituximab; difúzní velkobuněčný B-lymfom; vinkristin; Middle Aged; Retrospective Studies; prognóza; Antineoplastic Combined Chemotherapy Protocols; Treatment Outcome; Czech Republic; Aged, 80 and over; Cyclophosphamide; Lymphoma, Large B-Cell, Diffuse; Neoadjuvant Therapy; Rituximab; Recurrence; Young Adult; senioři nad 80 let; progrese nemoci; retrospektivní studie; Česká republika; mužské pohlaví; cyklofosfamid; Prognosis